Respostas fisiológicas e bioquímicas de plantas de milho (Zea mays L.) inoculadas com fungos micorrízicos arbusculares sob estresse salino - Pinto, Emanuelle Sampaio Almeida (2011)
Many studies have shown that inoculation with arbuscular mycorrhizal fungi improved plant growth under salt stress. Considering that the salinity is a serious problem that directly affects the productivity of plants, the aim of this study was to evaluate the effects of inoculation of AMF in maize plants under salt stress in the presence or absence of phosphorus. The experiment was run in a greenhouse of the Department of Biochemist and Molecular Biology of the Federal University of the Ceará (Campus of the Pici, Fortaleza - Ceará), with four replicates per treatment. The experimental design was completely randomized in factorial arrangement 2 (inoculated and not inoculated plants) x 3 (levels of salinity 0.5, 4.0 and 8.0 dS m-1) x 2 (presence or absence of phosphorus), total of 48 experimental units. During the experiment measurements were made of net photosynthesis, transpiration rate, stomatal conductance and SPAD index. At 40 days after sowing the plants, they were collected, and determined leaf area, shoot dry matter (after drying the material under glass), the relative water content, the osmotic potential, microbiological variables (dependency and mycorrhizal colonization), mineral levels (N, P, K+, Ca2+, Mg2+, Na+, and Cl-) and organic solutes (soluble carbohydrates, N-aminosolubles, proline and soluble protein). The mycorrhizal fungi did not provide an increase in the growth of corn plants, but elevated levels of salinity reduced leaf area and shoot dry matter of plants. Generally, the salinity reduced the photosynthesis, stomatal conductance and transpiration in all treatments. The relative water content was not influenced by any of the factors studied. The SPAD index and relative water content were not influenced by any of the factors studied. The osmotic potential was significantly reduced in treatments with 4.0 and 8.0 dS m-1 salinity compared with the level of 0.5 dS m-1. Mycorrhizal colonization decreased with increasing levels of saline. The levels of glomalin were not influenced by the presence of P and not by increasing levels of salinity. The mycorrhizal fungi did not cause increases in levels of inorganic solutes. The presence of P promoted maize cultivation in non-inoculated plants, increased levels of phosphorus in the leaves and stems, at all levels of salinity. Increased salinity levels decreased the levels of N and Mg2+, but promoted increased levels of Na+ and Cl- in corn plants. The water-soluble carbohydrate showed no significant differences for any of the factors. In general, the levels of N-aminosolubles and proline increased with increasing salinity. Since the levels of soluble proteins showed different responses according to the factors. These results suggest that the mycorrhizal fungi did not minimize the effects of salinity in maize plants (hybrid AG 1051), at least under the conditions employed here.